“CATUR KARANA” IDA BAGUS GEDE PURWA STUDY OF SANGGIT LAKON (KAWI CARITA) BALINESE SHADOW PUPPET - Widnyana, I Kadek; Sedana, I Nyoman; Sudarta, I Gusti Putu; Mawan, I Gede (Institut Seni Indonesia Denpasar, 2025)
Balinese Wayang kulit contains deep philosophy and aesthetics, with plays that are not only entertaining, but also contain moral teachings and life values. An important element in the structure of the play is the concept of